2016
DOI: 10.1111/cga.12133
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of cleft lip and/or palate in children from Lodz between years 1981–2010

Abstract: Congenital malformations constitute a serious problem of both medical and social nature. Cleft lip and/or palate represent the most common congenital anomaly of the face that is why it is essential to know the real frequency of the described phenomenon. The aim of this paper is to determine the frequency of cleft lip and/or palate and the types of malformations that occurred in Lodz city between the years 1981-2010. Our clinic has been carrying on the studies concerning the incidence of cleft lip and/or palate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 9 publications
(20 reference statements)
0
10
0
4
Order By: Relevance
“…31 For spatial distributions of the prevalence, we observed spatial heterogeneity of prevalence of cleft lip and/or palate across the study period in Guangdong province. For the prevalence of the disease in the world, previous studies showed that the figure was quite different, 8 which indicated that the distribution of the disease was unbalanced and there existed spatial heterogeneity globally. 28 For example, the prevalence was relatively high in East Asia and the pacific compared with other regions in the world.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…31 For spatial distributions of the prevalence, we observed spatial heterogeneity of prevalence of cleft lip and/or palate across the study period in Guangdong province. For the prevalence of the disease in the world, previous studies showed that the figure was quite different, 8 which indicated that the distribution of the disease was unbalanced and there existed spatial heterogeneity globally. 28 For example, the prevalence was relatively high in East Asia and the pacific compared with other regions in the world.…”
Section: Discussionmentioning
confidence: 99%
“…7 In many other regions, data on cleft lip and palate cases are of poor or incomplete quality, often lacking information on important variables such as gender and severity of morphological abnormalities, the published data on the prevalence of cleft lip and/or cleft palate from different parts of the world are quite different. 8 A previous study revealed that the African population had the lowest incidence of the disease, which is about 0.4/1000; in India, the average prevalence index of this disease was 0.398/1000 from 2007 to 2011. 9 Europe's incidence is about 1/1000; Asia and South Americas have relatively a high incidence of about 2/1000.…”
Section: Open Accessmentioning
confidence: 95%
See 1 more Smart Citation
“…Cleft lip and/or palate (CL/P) is a common birth defect of complex etiology. Asian populations have the highest reported birth incidence of 1/500 or higher (Natsume et al 2000;Seto et al 2003;Cooper et al 2006), while the reported incidence in European derived populations is around 1/1100 (Antoszewski and Fijałkowska 2016), and the reported incidence in African derived populations is 1/2500 (Ekanem et al 2008). There are no reports of epidemiological studies on congenital anomalies such as CL/P in the Lao People's Democratic Republic (Laos).…”
Section: Introductionmentioning
confidence: 99%
“…Em relação ao fenótipo, as fissuras de palato foram mais frequentes entre as mulheres e a fissuras de lábio isolada e de lábio com palato predominaram nos homens, características que corroboram os relatos de conjuntos de dados nacionais e mundiais (ANTOSZEWSKI;FIJAŁKOWSKA, 2016;COUTINHO et al, 2009;CUOZZO et al, 2013;FERRARI-PILONI;JESUÍNO, 2021;HLONGWA;LEVIN;RISPEL, 2019;IMPELLIZZERI et al, 2019;MARTELLI et al, 2012;MENEZES et al, 2010;PACÁKOVÁ et al, 2016;PANG;BROYLES;REDETT, 2013). Martelli et al (2012) (KIANIFAR et al, 2015), Austrália (LO et al, 2015) e China (FAN et al, 2018).…”
Section: Discussionunclassified